Keefektifan Koagualan Biji Asam Jawa (Tamaryndus Indica) Dalam Menurunkan Kadar Total Suspended Solid Pada Limbah Cair Industri Batik - Fashal Suwardi, Bambang; , Dwi Astuti, SKM., M.Kes (2017)
Research the use of Tamarind Seed (Tamaryndus Indica) as a natural coagulant in lowering levels of TSS (Total Suspended Solid) on the waste liquid of batik has been done. This research aims to analyze the effectiveness of addition of tamarind seeds powder (Tamaryndus Indica) using the method of coagulation in lowering levels of TSS (Total Suspended Solid) in liquid waste batik with a dose of 1 g/l g/l and 5 g/l. this research are experiments, using actual experimental design (True Experiment) and the design of the pretest and posttest whit control group. The total number of samplesin this research as many as 12 liters of liquid waste of batik. Research done in the laboratory of the Faculty of Health Sciences University of Muhammadiyah Surakarta. Technique of data analysis using statistical test Post Hoct Test LSD. The results showed: (1) the average levels of TSS (Total Suspended Solid) before treatment of 1660 mg/l and after treatment using coagulant tamarind seeds 0 g/l, 1 g/l, 2 g/l, and 3 g/l of 1360 mg/1900 mg/l, 620 mg/l and 433.4 mg/l; (2) a dose of coagulant tamarind seeds are most effective in lowering levels of TSS (Total Suspended Solid) waste liquid of batik is a dose of 3 g/l with the level of effectiveness of 73,89%.